(untitled) (Tạp chí Y học Cộng đồng, 2024)
Background: Postoperative inadequate analgesia is common and is associated with poor clinical outcomes. Perioperative pain management after orthopaedics surgery is still challenging. Moreover, the factors associated with severe pain that influence postsurgical pain control according to an acute pain protocol may underestimated and undermanaged, besides in the absence of reports representing Vietnam. Objective: This study aimed to identify the points pain score via the VAS and perioperative predictors of poor postoperative pain control in patients undergoing orthopaedics surgery. Method: The cross-sectional study was performed on patients in the Hospital for Traumatology and Orthopaedics HCMC from December 2023 to June 2024. Results: A total of 615 patients were included in this study. The means of VAS for the before and after orthopaedics surgery were 47.9±19.4 and 40.6±20.9, respectively, with statistically significant differences between the two assessment times (P < 0.05). Spinal surgery (OR = 4.63, 95%CI: 2.53-8.48) and ASA III/IV (OR = 2.78; 95%CI: 1.52-5.10) were statistically associated with severe pain (P < 0.05). Conclusion: In conclusion, there is an improved significantly between severe pain points by VAS between the first two interviews. Furthermore, we suggest that tightening management patients in ASA III/IV status and providing proper caring based on operative sites are promising approaches to reduce the severe postoperative pain rate.